Metodología para la enseñanza en el desarrollo de la velocidad traslación en jóvenes de 15 a 16 años - Murillo Rodríguez, Hector Adonis (2025)
The research focuses on the design of a methodology to teach the development of reaction speed in young people between 15 and 16 years old. Throughout the study, various problems related to the teaching of specific skills, such as speed, in educational institutions are identified. It is highlighted that, although general sports activities are promoted, the necessary attention is often not given to technical aspects such as travel speed. In addition, limitations are noted in the training of teachers, who do not have advanced strategies to teach this skill. The research also highlights the importance of adapting teaching to the individual needs of students, taking into account their physical, emotional and psychological conditions, especially in the case of those with health problems. The methodological proposal is based on a constructivist approach, which encourages meaningful learning through experience and reflection. Furthermore, the possibility of replicating this methodology in other educational institutions is highlighted, adapting it to the characteristics and resources available in each context, in order to promote a more inclusive physical education, particularly in low-resource communities.